An excited state managing molecular design platform of blue thermally activated delayed fluorescence emitters by π-linker engineering. Issue 5 (2nd January 2020) - Lee, Kyung Hyung; Jeon, Soon Ok; Chung, Yeon Sook; Numata, Masaki; Lee, Hasup; Lee, Eun Kyung; Kwon, Eun Suk; Sim, Myungsun; Choi, Hyeonho; Lee, Jun Yeob
Abstract : A molecular design platform of blue thermally activated delayed fluorescence (TADF) emitters to boost the external quantum efficiency and efficiency roll-off of blue TADF organic light-emitting diodes (OLEDs) was developed. Abstract : A molecular design platform of blue thermally activated delayed fluorescence (TADF) emitters to boost the external quantum efficiency and efficiency roll-off of blue TADF organic light-emitting diodes (OLEDs) was developed. A molecular structure hiring one or two excited state controlling subunits in the π-linker between a donor and an acceptor was employed. The subunit in the π-linker was a phenyl unit to precisely control the performances of TADF devices. It was described that the phenyl subunit simultaneously improved the external quantum efficiency and efficiency roll-off of TADF OLEDs. A high external quantum efficiency of 28.5% was demonstrated using the material design having two phenyl sub units.